Modeling of Electric Field Around 100 MVA 150/20 kV Power Transformator using Charge Simulation Method - Rachman, Noviadi Arief; Risdiyanto, Agus; Ramdan, Ade (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2013)
Charge Simulation Method is one of the field theory that can be used as an approach to calculate the electromagnetic distribution on the electrical conductor. This paper discussed electric field modeling around power transformator by using Matlab to find the safety distance. The safe distance threshold of the electric field to human health refers to WHO and SNI was 5 kV/m. The specification of the power transformator was three phases, 150/20 kV, and 100 MVA. The basic concept is to change the distribution charge on the conductor or dielectric polarization charge with a set of discrete fictitious charge. The value of discrete fictitious charge was equivalent to the potential value of the conductor, and became a reference to calculate the electric field around the surface contour of the selected power transformator. The measurement distance was 5 meter on each side of the transformator surface. The results showed that the magnitude of the electric field at the front side was 5541 V/m, exceeding the safety limits.